Effect of different parameters of Er:YAG laser irradiations on class V composite restorations: A scanning electron microscopy study. Issue 5 (11th January 2016) - Ozel, Emre; Tuna, Elif Bahar; Firatli, Sonmez; Firatli, Erhan
Summary: The purpose of this study was to compare different parameters of Er:YAG laser irradiations on the marginal microleakage of Class V resin composite restorations. A total of 45 extracted premolars were selected for the study. Class V cavities prepared on both buccal and lingual surfaces of teeth by Er:YAG laser or bur and divided into nine groups. The occlusal margins were in enamel and the cervical margins were in cementum. Group‐1: bur preparation; Group‐2: laser preparation (lp) (600 mJ/5 Hz); Group‐3: lp (300 mJ/10 Hz); Group‐4: lp (200 mJ/15 Hz); Group‐5: lp (150 mJ/20 Hz); Group‐6: lp (200 mJ/20 Hz); Group‐7: lp (300 mJ/14 Hz); Group‐8: lp (400 mJ/10 Hz); Group‐9: lp (700 mJ/5 Hz). All teeth were stored in distilled water at 37°C for 24 h, then thermocycled 1, 000 times (5–55°C). Five teeth from each group were chosen for the microleakage investigation and two teeth for the scanning electron microscope (SEM) evaluation. Teeth, which were prepared for the microleakage test were immersed in 0.5% methylene blue dye for 24 h. After immersing, the teeth were sectioned and observed under a stereomicroscope for dye penetration. Data were analyzed by Kruskal–Wallis and Mann–Whitney U tests (p < 0.05). More microleakage was observed in cervical regions compared to occlusal regions in all groups (p < 0.05) except for Group 6 (p > 0.05). No significant difference was observed among groups in terms of occlusal and cervical surfaces, separately (p > 0.05). It may be concluded that the cavities prepared by Er:YAG laser showed higher degree of microleakage than bur prepared at cervical regions. Different parameters of Er:YAG laser irradiations affected microleakage. SCANNING 38:434–441, 2016. © 2016 Wiley Periodicals, Inc.